Oil Market Power in General Equilibrium - Waldemar Marz; Johannes Pfeiffer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze monopoly power in a market for a complementary fossil resource like oil in a two country/two period model with international trade in general equilibrium. Focusing on the complex interplay of capital and resource market, we elaborate how these effects feed back into the resource monopolist's extraction decision. His level of knowledge about the economic structure thereby plays a key role. The accumulation of own capital assets over time, together with a recognized influence of extraction on the interest rate, can lead the monopolist to accelerate or postpone extraction. Considering the interaction of resource market and global capital accumulation poses an incentive for the monopolist to accelerate extraction and to exploit the importers' increased resource addiction in the future. The conservationist bias of resource market power can be increased, dampened or reversed through the general equilibrium effects.
Keywords: D42; D90; Q30; 330